AGROFORESTRY OF DRAGON FRUIT IN BUMI MULYO VILLAGE, EAST LAMPUNG REGENCY - Andhine Tri Prinanti; Indra Gumay Febryano; Hari Kaskoyo (Forestry Study Program University Of Mataram, 2026)
The development of dragon fruit through agroforestry plays an important role because it increases land cover, suppresses pests and diseases, and reduces capital costs compared to monoculture systems. This study aims to analyze the dragon fruit agroforestry systems developed in Bumi Mulyo Village, Sekampung Udik District, East Lampung Regency. A qualitative approach using a case study method was employed in this research. Data were collected through in-depth interviews, field observations, and document analysis. The collected data were analyzed to identify plant species and planting patterns in dragon fruit agroforestry systems. The results showed that the agroforestry system consisted of dragon fruit (Hylocereus polyrhizus) as the main crop; kapuk (Ceiba pentandra) as a living support tree and live fence tree; and several complementary plant species, namely avocado (Persea americana), cocoa (Theobroma cacao), mamey sapote (Pouteria sapota), black sapote (Diospyros nigra), durian (Durio zibethinus), papaya (Carica papaya), chili (Capsicum annuum), banana (Musa spp.), melinjo (Gnetum gnemon), and coconut (Cocos nucifera). The kapuk tree functions both as a living support tree for dragon fruit and as a live fence tree. Its leaves are also used by farmers as animal feed. The planting patterns applied by farmers include: (1) dragon fruit–kapuk; (2) dragon fruit–kapuk–avocado; and (3) dragon fruit–kapuk–fruit trees. These variations demonstrate farmers' adaptation in optimizing growing space to maximize the economic and ecological functions of the agroforestry system. Farmers are encouraged to develop more complex agroforestry systems from simple ones in order to increase income and support soil and water conservation.